2021
DOI: 10.3390/children8100848
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Confinement Due to COVID-19 on Physical Activity and Mediterranean Diet Adherence and Its Relationship with Self-Esteem in Pre-Adolescent Students

Abstract: Regular physical activity and good adherence to the Mediterranean diet are important for improving physical and mental health. Confinement due to the COVID-19 pandemic has led to a lack of exercise and poor nutrition. Preadolescent mental health, specifically regarding self-esteem, may have been affected. This is particularly relevant between the ages of 10 and 14. The influence of total confinement due to COVID-19 on physical activity and Mediterranean diet adherence, and its relationship with self-esteem was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 69 publications
2
16
0
1
Order By: Relevance
“…One major limitation of this cross-sectional study naturally concerns the use of a snowball sampling technique, which may possibly have contributed to selection bias, hampering the generalization of our findings to the pediatric population of both countries. It is plausible that, for instance, our overall favorable findings regarding dietary choices, arising mainly from children living in urban areas whose most caregivers had attended academic education, possibly indicating higher socioeconomic position, may not be straightforwardly representative of the habits of children from Spain and Portugal, particularly since earlier reports from Spain and Brazil have showed lower class isolated families presented lower consumption of healthy foods during the period of confinement [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…One major limitation of this cross-sectional study naturally concerns the use of a snowball sampling technique, which may possibly have contributed to selection bias, hampering the generalization of our findings to the pediatric population of both countries. It is plausible that, for instance, our overall favorable findings regarding dietary choices, arising mainly from children living in urban areas whose most caregivers had attended academic education, possibly indicating higher socioeconomic position, may not be straightforwardly representative of the habits of children from Spain and Portugal, particularly since earlier reports from Spain and Brazil have showed lower class isolated families presented lower consumption of healthy foods during the period of confinement [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 90%
“…To date, as far as we know, only one study has studied parental perception of children’s oral hygiene during lockdown in Portugal [ 31 ]. On the other hand, some reports from Spain have explored the influence of confinement on diet and other lifestyle behaviors, though not focusing specifically on oral health matters [ 27 , 30 ]. In the current study, a wide variety of work status was observed among caregivers during the lockdown and most of the children cohabited with siblings throughout this period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trigueros et al [ 37 ] state that the subject of physical education helps the physical and healthy development of the adolescent population. Likewise, Melguizo-Ibáñez et al [ 38 ] together with Villodres et al [ 10 ] establish that the socioeconomic level of families also influences young people’s active and healthy lifestyles, with parents being a fundamental element in promoting these lifestyles. Positive relationships have also been found between physical activity and emotional intelligence.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition is supposed to play a fundamental role in the development and growth of different subjects [ 3 ]; however, during this stage, due to the biological, psychological and social changes that take place, human growth and development can be affected in a negative way [ 9 ]. In view of this problem, the Mediterranean diet is considered a healthy dietary model due to its contribution to optimal health and quality [ 10 ]. This dietary pattern is characterised by a wide variety of foods, such as wholegrain cereals, olive oil, bread, milk and dairy products, fruit, vegetables, and nuts [ 11 ].…”
Section: Introductionmentioning
confidence: 99%